2015
DOI: 10.1007/s12032-015-0576-0
|View full text |Cite
|
Sign up to set email alerts
|

SDF-1/CXCR4 promotes F5M2 osteosarcoma cell migration by activating the Wnt/β-catenin signaling pathway

Abstract: Osteosarcoma (OS), the most common primary malignant bone tumor in children and adolescents, lacks an effective therapy. Stromal cell-derived factor (SDF-1) and its receptor, CXCR4, play multiple roles in migration, proliferation, and survival of different tumor cells. This study aimed to investigate whether the functional SDF-1/CXCR4 signaling mediates chemotaxis in F5M2 OS cells as well as the underlying mechanisms. Immunohistochemistry and immunofluorescence microscopy were used. RNA expression was detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
3
5
0
Order By: Relevance
“…In the present study, the suppression of CXCR4 expression also decreased the protein expression of β-catenin targeting genes (MMP-2 and c-myc). Our results confirmed the previously established role of the CXCR4/β-catenin axis in the malignant progression of cancers (18)(19)(20).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, the suppression of CXCR4 expression also decreased the protein expression of β-catenin targeting genes (MMP-2 and c-myc). Our results confirmed the previously established role of the CXCR4/β-catenin axis in the malignant progression of cancers (18)(19)(20).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have demonstrated that SDF-1/CXCR4 may induce cancer cell proliferation, and invasion through activation of the Wnt/β-catenin signaling pathway (18)(19)(20). Specifically, the Wnt/β-catenin signaling pathway is a key modulator of cellular proliferation (21).…”
Section: Introductionmentioning
confidence: 99%
“…The PI3K/Akt and mitogen-activated protein kinase (MAPK)/ERK signal transduction pathways, which are mediated by SDF-1, contribute to cell migration, proliferation, tube formation, apoptosis and chemotaxis (26,27). For example, SDF-1-induced Akt and ERK activation results in lung cancer cell invasion and metastasis (28), sacral chondrosarcoma and glioblastoma cell cycle progression and epithelial-mesenchymal transition (29,30), as well as ovarian cancer cell proliferation (31), and pre-B (26), F5M2 osteosarcoma (32) and epitheloid carcinoma (33) cell migration. It has been reported that SDF-1 serves a critical role in the regulation of EPC cellular functions, including cell proliferation and migration (23,34).…”
Section: Introductionmentioning
confidence: 99%
“…CXCL12 is also called stromal cell-derived factor-1 ( SDF-1) and can bind to G-protein-coupled chemokine receptor CXCR4 ( Nagasawa, 2014 ). Increasing studies suggested that CXCL12 /CXCR4 axis played pivotal roles in tumor growth and development ( Balkwill, 2004 ; Lu et al., 2015 ; Perissinotto et al, 2005 ). Li et al (2018) .…”
Section: Discussionmentioning
confidence: 99%